# To express: The function F ( x ) = ( 2 x + x 2 ) 4 in the form of ( f ∘ g ) ( x ) . ### Single Variable Calculus: Concepts...

4th Edition
James Stewart
Publisher: Cengage Learning
ISBN: 9781337687805 ### Single Variable Calculus: Concepts...

4th Edition
James Stewart
Publisher: Cengage Learning
ISBN: 9781337687805

#### Solutions

Chapter 1.3, Problem 41E
To determine

## To express: The function F(x)=(2x+x2)4 in the form of (f∘g)(x) .

Expert Solution

The function F(x)=(2x+x2)4 can be expressed as F(x)=f(g(x)), where  f(x)=x4 and g(x)=2x+x2 .

### Explanation of Solution

The given composite function is F(x)=(2x+x2)4 .

Name the expression 2x+x2 as g(x)=2x+x2 .

Thus, F(x)=(g(x))4 .

It can be expressed as F(x)=f(g(x)) as F(x) is a composition of f and g.

Replace g(x) by x to obtain the expression for f(x) .

Therefore, f(x)=x4 .

Hence, it can be concluded that F(x)=(2x+x2)4 can be expressed as F(x)=f(g(x)), where  f(x)=x4 and g(x)=2x+x2 .

Verification:

The composite function (fg)(x) is defined as follows.

(fg)(x)=f(g(x))

Substitute 2x+x2 for x in f(x) .

f(2x+x2)=(2x+x2)4=F(x)

Thus, it is verified that F(x)=(2x+x2)4 can be expressed as F(x)=f(g(x)), where  f(x)=x4 and g(x)=2x+x2 .

### Have a homework question?

Subscribe to bartleby learn! Ask subject matter experts 30 homework questions each month. Plus, you’ll have access to millions of step-by-step textbook answers!